A maternally derived complex small supernumerary marker chromosome involving chromosomes 8 and 14: case report and review of the literature - Ouboukss, Fatima; El Amrani, Zhour; Bouchahta, Hicham; Ratbi, Ilham; Sbiti, Aziza; Liehr, Thomas; Sefiani, Abdelaziz; Natiq, Abdelhafid (Frontiers in Genetics, 2024)
The majority of small supernumerary marker chromosomes (sSMCs) are derived from one single chromosome. Complex sSMCs, on the other hand, consist of genetic material derived from more than one, normally two chromosomes. Complex sSMCs involving chromosomes 8 and 14 are rarely encountered.We present here a 14-month-old boy born from an unrelated couple. At birth, the baby was hypotonic and had a cleft lip and palate, as well as ocular involvement. Throughout the course of development, the baby experienced feeding difficulties, stunted growth, and delayed psychomotor development. Banding together with molecular cytogenetics revealed a balanced maternal translocation t(8;14)(p22.3;q21)mat, leading due to meiotic 3:1 segregation to a partial trisomy of chromosomes 8 and 14 in the affected boy.This report highlights the importance of cytogenetics in diagnosis of rare genetic disorders, with impact on genetic counselling of patients and their families. There are three comparable cases in the literature involving both chromosomes 8 and 14, but with different breakpoints; the complex sSMC derived from chromosomes 8 and 14 in this case, characterized as der(14)t(8;14)(p22.3;q21)mat.